Architecture and Kinematics of the Constance‐Frick Trough (Northern Switzerland): Implications for the Formation of Post‐Variscan Basins in the Foreland of the Alps and Scenarios of Their Neogene Reactivation. Issue 7 (25th July 2018) - Madritsch, Herfried; Naef, Henry; Meier, Beat; Franzke, Hans Joachim; Schreurs, Guido
Abstract: Post‐Variscan basins are commonly inferred to represent important precursor structures of later extensional and contractional tectonic events in the foreland of the European Alps. Nevertheless, their structural characteristics are typically poorly constrained. Our investigation sheds new light on the architecture and kinematics of the Constance‐Frick Trough (CFT) in Northern Switzerland. According to our analysis of an extensive and revised 2‐D reflection seismic data set, the ENE‐WSW striking CFT is divided into an eastern segment and a western segment characterized by opposing half‐graben geometries. The transition between the two segments coincides with the prolongation of a preexisting WNW‐ESE trending strike‐slip fault zone exposed in the adjacent Black Forest Massif to the north. Field‐based analysis of outcrop‐scale faults in the latter area implies that the minimum horizontal stress during the formation of the CFT was roughly oriented NE‐SW, which is oblique to the trough axis. While previously published analogue models imply that some characteristics of the CFT could be explained by lateral linkage of graben segments under oblique extension, the pronounced half‐graben geometry of the CFT suggests that low‐angle normal faulting may also have contributed to trough formation. The observed structural complexities of the CFT and uncertainties regarding its deep structure must be taken into account for interpretations of similar Late Paleozoic basins inferred in the subsurface of the northern Alpine foreland basin, in particular, concerning scenarios of their Neogene reactivation during Alpine orogeny. Key Points: Two‐dimensional seismic data constrain the along‐strike segmentation of a major Late Paleozoic basin in the northern Alpine foreland Field data underline the signficance of extension obliquity for basin formation The structural complexities and uncertainties of Late Paleozoic basins must be considered in scenarios of their Neogene reactivation